Field evaluation of botanical and biorational insecticides for sustainable management of Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) in potato cultivation - El Aalaoui, Mohamed; Kamal, Fatima Zahra; Rammali, Said; Ciobica, Alin; Albert, Cristina; Novac, Bodgan; Burlui, Vasile; Sbaghi, Mohamed (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe potato tuber moth Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) is a major pest threatening potato crops worldwide.MethodsThis study evaluated the effectiveness of 12 treatments—including biorational insecticides, plant extracts, and their combinations—over 2 years (2024 and 2025) under field conditions. Treatments included Spinosad (200 cc/hL) (SD), mineral oil (1,000 cc/hL) (MO), potassium salts of fatty acids (300 cc/hL) (PFA), Nicotiana glauca (NG) and Ricinus communis (RC) extracts (10% w/v), and their combinations. Applications were made five times per year, starting 3 weeks after planting and repeated every 3 weeks, using a randomized complete block design with two replicates. Parameters measured included leaf damage, larval density, canopy area, tuber number, tuber weight, and total yield.Results and DiscussionThe combination of mineral oil with R. communis consistently resulted in the lowest leaf damage, reducing it to 18.2 and 15.8% at 3 months after the first treatment (MAFT) in 2024 and 2025, respectively. Larval density was also suppressed, with MO + RC reducing larvae to 1.5 (2024) and 1.2 (2025) per plant at 3 MAFT. Canopy area remained stable across treatments in 2024 but decreased significantly in Spinosad combinations in 2025. The highest tuber number (9.4 and 9.16 per plant) and tuber weight (160.85 g and 158.73 g) in 2025 were recorded with MO + NG and MO + RC treatments. Total tuber yield peaked at 43.5 t/ha with MO + NG. These results demonstrate the superior efficacy of mineral oil combined with botanical extracts in reducing pest damage and improving potato productivity.